CRANIOMETRY OF THE FACIAL PART OF THE SKULL - Киселева, Елена Александровна; Иванова, Ольга Павловна; Черненко, Сергей Владимирович; Корчемная, Ольга Сергеевна; Корчемный, Владимир Маркович; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; Центер, Яэль (Medicine in Kuzbass, 2023)
This article is devoted to the problem of studying the connections of the maxillary system with other parts of the face and skull using computer tomography. The authors carried out measurements of latitudinal, diagonal parameters, and also calculated the depth of the upper and lower gnatic parts of the face relative to the bone landmarks. The indices of the correspondence of the parameters of the craniofacial complex to the parameters of the dental arches due to the absence of soft tissues of the facial part of the skull were determined. For example, according to computed tomography, it was found that the compliance index obtained with the ratio of the depth of the gnatic part of the upper part of the face (GGCHLv.o.) to the depth of the dental arch of the upper jaw (Dd1-7v.h.) is 2.3 ± 0.025. With the ratio of the depth of the gnatic part of the lower face (GGCHLn.o.) to the depth of the dental arch of the lower jaw (Dd1-7n.h.), an index of 2.5 ± 0.013 was obtained.